2015
DOI: 10.1038/nn.4114
|View full text |Cite
|
Sign up to set email alerts
|

Stress effects on the neural substrates of motivated behavior

Abstract: Exposure to stress has profound, but complex, actions on motivated behavior and decision-making. These effects are central to core symptoms of a number of psychiatric disorders that are precipitated or augmented by stress, such as depressive disorders and substance use disorders. Studying the neural substrates of stress’s effects on motivation has revealed that stress affects multiple targets on circuits throughout the brain using diverse molecular signaling processes. Moreover, stress does not have unitary ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(87 citation statements)
references
References 99 publications
(63 reference statements)
1
85
0
1
Order By: Relevance
“…Stress exposure can initiate a neuroendocrine cascade that modulates how individuals perceive and respond to rewarding or threatening cues in their environment (411). Specifically, it has been shown that stress may reduce acquisition of reward-related information (8, 12, 13) as well as disrupt normal reinforcer devaluation (9, 14, 15), two phenomena that are commonly observed in stress-related psychiatric disorders (1620).…”
Section: Introductionmentioning
confidence: 99%
“…Stress exposure can initiate a neuroendocrine cascade that modulates how individuals perceive and respond to rewarding or threatening cues in their environment (411). Specifically, it has been shown that stress may reduce acquisition of reward-related information (8, 12, 13) as well as disrupt normal reinforcer devaluation (9, 14, 15), two phenomena that are commonly observed in stress-related psychiatric disorders (1620).…”
Section: Introductionmentioning
confidence: 99%
“…Acute stress-related increases in glucocorticoids are critical both for the alarm signal as well as in regaining control over the stress signal resulting in healthy stress coping. Recent animal data show a glucocorticoid role in modulation of the medial PFC involved in goal-directed behaviors (54). Interestingly, the highly significant negative association between stress-related cortisol increases and reduced rACC/VmPFC was for the S-N average rACC/VmPFC response and not for the dynamic changes that were found to be correlated with active coping.…”
Section: Discussionmentioning
confidence: 92%
“…inhibition in AN-BP could reflect the consequences of prolonged, extreme stress, namely significantly low weight, which engenders various cognitive and neuroendocrine perturbations (57,58). Interestingly, preclinical research has identified disrupted dopaminergic signaling following severe stress (59,60); however, the effect of stress on dopaminergic projections to prefrontal cortex remains understudied. The dearth of research in this area discourages a premature interpretation of our stress induction effects in AN-BP.…”
Section: Stress-induced Reductions In Prefrontal Responses During Botmentioning
confidence: 99%